Morphological characteristics of sex dimorphism in Gobiopterus sp. (Gobiiformes: Oxudercidae) from Ranu Grati Lake, Pasuruan District, East Java, Indonesia - SEPTI ANITASARI; DIANA ARFIATI; SUSILO SUSILO; AGUNG PRAMANA WARIH MARHENDRA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Anitasari S, Arfiati D, Susilo, Marhendra APW. 2024. Morphological characteristics of sex dimorphism in Gobiopterus sp. (Gobiiformes: Oxudercidae) from Ranu Grati Lake, Pasuruan District, East Java, Indonesia. Biodiversitas 25: 1214-1222. Ranu Grati is a volcanic lake located in Pasuruan, East Java, Indonesia which has high ecological value as a habitat for a unique endemic fish found only in this lake, namely the Lempuk fish (Gobiopterus sp.). The aim of this research is to determine the morphological characters based on sexual dimorphism of Lempuk fish. in Ranu Grati Lake. The result showed the body color of male and female Lempuk fish is transparent. Lempuk fish do not have sexual dichromatism or their sex cannot be distinguished based on their body color. Lempuk fish have vomer teeth and canine teeth. Types of male and female ctenoid scales have a comb-like shape. The position of the mouth of the Lempuk Fish is located near the top or head of the fish but not precisely at the tip. There are variations in the superior subterminal mouth type between male and female fish, especially in terms of anatomical details and mouth structure. Based on meristic observations of the Lempuk fish, it can be explained that this fish has a fusiform body shape, this shows that gobies generally have a small fusiform body and also has pectoral fins, pelvic fins, dorsal fins, tail fins and anal fins. In this study, we found from histological observations of the Lempuk fish, mature oocytes and spermatids were found in one histological tissue sample at male fish with gonad maturity level II. This change from female to male occurs at the size of the fish with fish size of 21.21-30.58 ± 2.14mm. It indicates that is Lempuk fish is a species hermaphrodite protogyn.